Amulets and charms of the peoples of the Northwestern Caucasus in the Russian Museum of Eth-nography collection - Ritsa Sh. Zelnitskaya (Кавказология, 2023)
The article examines objects from the Russian Ethnographic Museum’s collection, the primary purposes of which are protective. The collection of things with defensive or protective properties dates back to the first museum excursions to the Caucasus and is still going on today. Researchers frequently turn to the study of magical activities that are a vital component of traditional societies’ lives. The study discovered that amulets and amulets identical to each other existed in the North-Western Caucasus, regardless of the prevalent religion of the region’s peoples. Items from the REM collection, which represent all forms of amulets and amulets that existed here, are the primary source of work. The article also depends on the works of predecessors devoted to the spiritual culture of the peoples of the Northwestern Caucasus, as well as field materials gathered by the author throughout many years of anthropological expeditions to the region under investigation. The author concludes that: 1) when creating amulets, the religious affiliation of the peoples of the North-Western Caucasus is of secondary importance; 2) despite belonging to world religions - Islam or Christianity - people use individual objects to protect themselves and the space around them from harmful effects; and 3) any object that has been given sacred significance can be used as a protective object. The study’s findings demonstrate the Caucasus as a place where peoples have constantly interacted, resulting in reciprocal enrichment of civilizations.